2020
DOI: 10.1371/journal.pone.0233535
|View full text |Cite
|
Sign up to set email alerts
|

The Community Navigator Study: Results from a feasibility randomised controlled trial of a programme to reduce loneliness for people with complex anxiety or depression

Abstract: BackgroundLoneliness is common among people with mental health problems and predicts poorer recovery from depression and anxiety. Needs for support with loneliness and social relationships are often under-addressed in mental health services.The Community Navigator programme was designed to reduce loneliness for adults (aged 18 and above) with complex depression or anxiety who were using secondary mental health services. Acceptability and feasibility of the programme and a trial evaluation were tested in a feas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
47
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 36 publications
(47 citation statements)
references
References 27 publications
0
47
0
Order By: Relevance
“…There are a number of interventions that are thought to have the potential to affect the number or quality of social relationships which might be particularly worth investigating; these include Interpersonal Psychotherapy, 39 Dynamic Interpersonal Therapy, 40 and work with Community Navigators. 41 Further, future studies might investigate the impact of offering more regular reviews and more intensive treatments to those reporting a severe lack of social support, in order to mitigate the risk of poor prognosis.…”
Section: Implications and Conclusionmentioning
confidence: 99%
“…There are a number of interventions that are thought to have the potential to affect the number or quality of social relationships which might be particularly worth investigating; these include Interpersonal Psychotherapy, 39 Dynamic Interpersonal Therapy, 40 and work with Community Navigators. 41 Further, future studies might investigate the impact of offering more regular reviews and more intensive treatments to those reporting a severe lack of social support, in order to mitigate the risk of poor prognosis.…”
Section: Implications and Conclusionmentioning
confidence: 99%
“…This paper explores the views of programme participants: we acknowledge that other stakeholders, including the Community navigators, and involved family and mental health staff, might also have useful perspectives on factors influencing participation in the programme. A summary of stakeholders’ views on the acceptability of the programme has been reported elsewhere [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…The study involved three phases: development of the programme using a co-production approach [ 27 ]; preliminary testing of the programme with ten service users with severe depression and/or anxiety on the caseload of one of two community mental health teams; and a feasibility trial of the programme involving 40 service users from the same community teams. A full description of the Community Navigator programme [ 26 ], and results of the feasibility trial have been published [ 28 ].…”
Section: Methodsmentioning
confidence: 99%
“…The study involved three phases: development of the programme using a co-production approach (24); preliminary testing of the programme with ten service users with severe depression and/or anxiety on the caseload of one of two community mental health teams; and a feasibility trial of the programme involving 40 service users from the same community teams. A full description of the Community Navigator programme, and methodological details of the feasibility trial are reported in the published protocol (23); results of the feasibility trial have also been published (25).…”
Section: The Community Navigator Studymentioning
confidence: 99%
“…This paper explores the views of programme participants: we acknowledge that other stakeholders, including the Community navigators, and involved family and mental health staff, might also have useful perspectives on factors in uencing participation in the programme. A summary of stakeholders' views on the acceptability of the programme has been reported elsewhere (25).…”
Section: Strengths and Limitationsmentioning
confidence: 99%